Transitional justice: images and memories - Brants, Chrisje; Hol, Antoine; Siegel, Dina (Advances in criminology, 2013)
Introduction / Chrisje Brants -- The question of Turkey : contested, forgotten and remembered memories / Gulhan Demirci -- The lives and times of sentenced Nazi war criminals : re-negotiating guilt and innocence in post-Nuremberg Germany 1950- 1975 / Susanne Karstedt -- René Cassin, state sovereignty and transitional justice in the period of the Second World War / Jay Winter -- The theater of justice : on the educational meaning of criminal trials / Antoine Hol -- Memory culture and urban reconstruction : the case of Staro Sajmište in Belgrade / Srdjan Radovic -- Transitional justice and local memory : commemoration and social action in Londres 38, espacio de memorias / Katrien Klep -- The role of ritual is shifting collective dispositions / Danielle Celermajer -- Communicating the ICC : imagery and image-building in Uganda / Chrisje Brants, Kees Brants & Lauren Gould -- Child soldiers : towards a rights-based imagery / Ton Liefaard -- Images of international criminal justice in the former Yugoslavia / Sanja Kutnjak Ivković -- Wagner in Israel : the mixture of politics and music / Dina Siegel -- 'Maybe if the world had paid more attention' : western cinematic perspectives on the Rwandan genocide and the role of the west: Hotel Rwanda, Shooting Dogs and Sometimes in April / Bernadette Kester -- An eye for an eye : the imagery of the 1947 partition (India, Pakistan) / Lodewijk Brunt